Major cardiovascular events and associated factors among routine hemodialysis patients with end-stage renal disease at tertiary care hospital in Somalia - Farah Yusuf Mohamud, Mohamed; Nur Adan, Faduma; Osman Omar Jeele, Mohamed; Ahmed, Mohamed A. M. (Frontiers in Medicine, 2023)
Introduction Cardiovascular complications are the most significant cause of death in patients undergoing routine hemodialysi (HD) with end-stage renal disease (ESRD). The main objective of this study is to determine the significant cardiac events and risk factors in patients undergoing routine hemodialysis in Somalia. Methods We carried out a cross-sectional retrospective study in a single dialysis center in Somalia. Two hundred out of 224 were included. All of them had ESRD and were on hemodialysis during the study period between May and October 2021. The records of all patients were reviewed, and the following parameters were analyzed socio-demographic factors, risk factors for cardiovascular disease, and the presence of cardiovascular diseases. Results The mean age was 54 ± 17.5 years (range 18–88 years), and 106 (53%) patients were males. The prevalence of a cardiovascular disease among hemodialysis patients was 29.5%. Moreover, the distribution of cardiovascular diseases was different; heart failure was the most common, about 27.1%, followed by coronary artery disease (17%), pericarditis and pericardial-effusion (13.6%), dysrhythmia (10.2%), cerebrovascular-accident (8.5%), and peripheral vascular disease (3.4%). About 176 (88%) participants had at least one modifiable cardiovascular risk factor. The most common modifiable cardiovascular risk factor was hypertension (n = 45, 25.1%), followed by anemia (n = 28, 15.6%) and diabetes (n = 26, 14.5%). Younger (18–30) participants were six times less likely to have cardiovascular events among hemodialysis than older age 0.4 (0.11–1.12). Conclusion Low prevalence rate of cardiovascular complications was confirmed in ESRD patients receiving hemodialysis in the main HD center in Somalia. Diabetes, anemia, and hypertension were the highest significant risk factors for CVD in HD patients with ESRD in Somalia.